Sharia Supervisory Board: A Review and Some Finding - Aam (SMART Insight, 2021)
This study reviews research on the Sharia Supervisory Board (SSB) role in Scopus indexed journals. This analysis uses descriptive statistical analysis based on 116 selected papers related to the Sharia Supervisory Board role from national and international journals. All samples of published journals have been published from 2010 to 2021. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric visualization map to develop Sharia Supervisory Board role research. The results of this bibliometric mapping research show a map of the development of research in the field of Sharia Supervisory Board role. The most popular keywords are Sharia Supervisory Board, Islamic Banking, Shariah Governance, and Islamic Financial Institution. The most popular author is Alam M.K. The most popular institution is the Faculty of Economics and Management Sciences International Islamic University Malaysia. The most popular country is Malaysia. In addition, this study also finds that the role of the Sharia Supervisory Board in an Islamic Financial Institution is very urgent in ensuring sharia compliance.